2018
DOI: 10.1111/famp.12390
|View full text |Cite
|
Sign up to set email alerts
|

Treatment‐as‐Usual for Couples: Trajectories Before and After Beginning Couple Therapy

Abstract: Couple therapy has been shown to be a meaningful way to improve couples’ relationships. However, less information is known about couples’ functioning prior to entering treatment in community settings, as well as how their relationship functioning changes from initiating therapy onward. This study examined 87 couples who began community‐based couple therapy during a longitudinal study of couples in the military. The couples were assessed six times over the course of 3 years, including time points before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
(72 reference statements)
1
5
0
2
Order By: Relevance
“…Specifically, mean effect sizes of change were small to moderate in the current study (0.18 < d < 0.49) and roughly twice as large in magnitude as observed among waitlist/control couples in studies of couple therapy (Roddy et al, 2020). These differences may be due to the fact that couples who seek couple therapy generally do so only after an extended period of distress (e.g., Owen et al, 2019), suggesting that their distress may be more stable than that observed in community samples or than that among the many couples who pursue alternate forms of assistance for their relationship such as the online services studied here (Stewart et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Specifically, mean effect sizes of change were small to moderate in the current study (0.18 < d < 0.49) and roughly twice as large in magnitude as observed among waitlist/control couples in studies of couple therapy (Roddy et al, 2020). These differences may be due to the fact that couples who seek couple therapy generally do so only after an extended period of distress (e.g., Owen et al, 2019), suggesting that their distress may be more stable than that observed in community samples or than that among the many couples who pursue alternate forms of assistance for their relationship such as the online services studied here (Stewart et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, because the sample sizes were relatively small (ranging from 5 to 33 in Baucom and from 5 to 20 in Roddy), estimates were less robust and there was less power to detect effects. Second, partners seeking couple therapy are likely to be quite distressed and typically only seek treatment after an extended period of declining relationship functioning (e.g., Jarnecke et al, 2020; Owen et al, 2019). This suggests that this group may be especially unlikely to improve (and arguably makes it striking that the mean pattern was one of stability) and that they may not represent all “help‐seeking couples.” Indeed, it is more common for distressed help‐seeking couples to seek assistance for their relationship through means other than couple therapy, including reading self‐help books, looking up information online, or seeking advice from friends or family (Stewart et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown changes in satisfaction from pre- to posttreatment and follow-up (i.e., Christensen et al, 2010; Nowlan et al, 2017; Seiter et al, 2020; Tilden, Theisen, et al, 2020). Owen et al (2019) had a unique opportunity to investigate the trajectories of relationship satisfaction before seeking treatment and after. In a sample of military couples who participated in relationship education and were followed over a 10-year period, the researchers were able to investigate couples who indicated they had sought couple therapy during the follow-up data collection waves.…”
Section: A Common Factors Approachmentioning
confidence: 99%
“…In our model, we did not include therapist as a level because it was not possible to have a reliable estimate of therapist effect as a level due to a small sample size and the large number of therapists. Although piecewise models allow testing hypotheses on level change which represents change in mean level at a particular time point (Owen et al, 2019), we assumed only change in slope in this study, which represents improvement from pre-to posttreatment and maintenance in the follow-up period. TC had a large number of missing data (A total n = 63; missing data = 28 to 38 for any one TC) because patients listed TCs at the end of treatment that did not match those they had listed at pretreatment.…”
Section: Multilevel Modelingmentioning
confidence: 99%